CULTURAL DIFFERENCE IN ENGLISH AND UZBEK MASS-MEDIA ADVERTISING: PRAGMATIC APPROACH - Jontemirova Yulduz Nu'mon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article delves into the intricate realm of mass-media advertising, specifically exploring the cultural nuances present in English and Uzbek advertising landscapes through a pragmatic lens. In an era of globalization, understanding how advertising messages are constructed, interpreted, and responded to within distinct cultural contexts is imperative for marketers aiming to effectively engage diverse audiences. By applying principles of pragmatics, this study seeks to elucidate the underlying cultural differences that shape advertising strategies and consumer perceptions in both English speaking and Uzbek-speaking regions. Through an analysis of language use, visual imagery, and cultural references, this thesis aims to contribute to a deeper understanding of how cultural factors influence advertising practices and consumer behavior on a global scale.